A biodegradable functional water-responsive shape memory polymer for biomedical applications. Issue 1 (5th December 2018) - Guo, Yifan; Lv, Ziying; Huo, Yiru; Sun, Lijie; Chen, Shuo; Liu, Zenghe; He, Chuanglong; Bi, Xiaoping; Fan, Xianqun; You, Zhengwei
Abstract : A biodegradable water-responsive shape memory polymer, which can be readily functionalized. Abstract : Shape memory polymers (SMPs) have exhibited great potential in biomedical applications. However, the typical triggers of shape recovery such as heat, UV light, and electricity may be harmful to humans. Accordingly, water-responsive SMPs have become significant, especially for in vivo applications, due to the intrinsic biocompatibility and ready availability of water. However, the reported water-responsive SMPs are limited and relatively complicated. Here, we design a new water-responsive SMP, poly(butanetetrol fumarate) (PBF); the properties of PBF could be modulated by curing. The cured PBF scaffolds exhibited high shape recovery and fixity rates (>95%). PBF showed good biodegradability, and it could support the attachment, viability and alkaline phosphatase activity of osteoblasts. Furthermore, PBF could be readily functionalized via pendant hydroxyl groups, which was demonstrated by the immobilization and controlled release of bone morphogenetic protein 2. We expect that PBF will be useful for various biomedical applications including water-responsive scaffolds, sensors or actuators.